(untitled) (CIPEEX, 2025)
The aim of this abstract was to describe the difference between monocytes and macrophages in the immune response. The immune system plays a crucial role in defending against pathogens, renewing cells, and removing damaged or neoplastic cells. Monocytes and macrophages are key players in innate immunity, known for their phagocytic ability and role in linking innate and adaptive immunity. Innate immunity provides a quick response to pathogens without prior exposure, acting as the body’s first defense line. Adaptive immunity develops over time, involving B and T lymphocytes responsible for humoral and cellular immunity, respectively. Monocytes circulate in the blood and migrate to tissues, differentiating into macrophages or dendritic cells. These cells phagocytize pathogens, present antigens to T cells, and regulate inflammation through mechanisms such as phagocytosis and opsonization. Their interaction with other immune components is critical for effective defense, inflammation resolution, and tissue homeostasis. Understanding these mechanisms is key to advancing therapeutic approaches and maintaining immune balance.